Tools & tillage. ([Copenhagen Gyldendal, etc., 1968)
Annual
English or German with summaries in the other languages.
Keywords: Agricultural implements -- History -- Periodicals; Agriculture -- History -- Periodicals; Tillage -- History -- Periodicals; Traditional farming -- History -- Periodicals